Religiosity and Credibility of the Bids and Awards Committee (BAC) of the Civil Aviation Authority of The Philippines (CAAP) - Genuba, Rinante; Macahilig, Caesar; Dura, Alger P. (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aimed to establish the significant influence of religiosity on the credibility of the Bids and Awards Committee of the Civil Aviation Authority of the Philippines. There were 300 respondents in this study chosen through the random sampling technique. Respondents were the members of the Bids and Awards committees, office personnel, suppliers, and bidders of the Civil Aviation of the Philippines, excluding the rest of the aviation employees not involved in the procurement system of CAAP. A non-experimental quantitative design utilized a descriptive correlational technique to gather data. Statistics used in data analysis were the mean and standard deviation, Pearson r, and regression analysis. Results showed a very high level of religiosity and a high level of credibility among the respondents. In addition, the correlation test revealed a significant positive relationship between religiosity and credibility. Furthermore, the regression analysis revealed the overall influence of religiosion to credibility. When regressed individually, it was found that responsibility best predicts credibility.